ANALISIS KINERJA APARATUR PEMERINTAH KECAMATAN DALAM MEMBERIKAN PELAYANAN PUBLIK DI KANTOR CAMAT MEDAN DENAI - Sadat, Anuar (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2019)
This study aims to analyze the extent of the performance of the district apparatus in providing public services based on the following indicators; tangible, reliability, responsiveness, assurance and empathy. The research location is Denai Medan District Office and uses quantitative descriptive methods that involves a research population consisting of all office employees totaling 42 (forty two) people. The results showed that respondents with the five indicators mentioned were related to the quality of service performance, and it showed the following percentages; the largest percentage is related to service reliability with an average of 88.57% and is a very satisfying category, followed by the second, which is related to responsiveness of 86.50% and is a very satisfying category. While the third place is about real service, which is 83.68% included in the very satisfying category. Furthermore, the fourth rank is related to service guarantee with a value of 80.35% and is a satisfactory category. The fifth is related to empathy services which is 70.24% in the satisfactory category.